Common complications post-kidney transplantation: a literature review - Al-Amri, Talal M.; Alharthi, Yousef H.; Alkhamis, Abdullah S.; Muhaif, Ali I. Al; Almutairi, Mohammad A.; Mousa, Narjes M. Al; Awkar, Ali A.; Yahya, Nawaf A.; Abbas, Wajdi I.; Nass, Omar A.; Alibrahim, Dhiyaa A. (International Journal Of Community Medicine And Public Health, 2021)
The most efficacious management modality for patients with end-stage renal disease is kidney transplantation. Although dialysis of the conditions and obstacles might be a temporary solution, it has been previously correlated with increased risk of many complications, including mortality and reduced health-related quality of life. In this literature review, the aim to discuss the commonly reported complications of post-kidney transplant, including complications that are usually caused by immune-mediated pathologies and non-immunological. Nevertheless, allograft rejection post-kidney transplant is the most common reported immunological complication following transplantation because it can be acute, subacute, accelerated, or chronic. However, after induction of the immunosuppressive modalities, the rates of graft rejections were significantly reduced but many other drug-related complications and have emerged as post-transplantation DM, malignancies, cardiovascular diseases, and infections. Many risk factors for developing post-transplant DM have been reported in the literature, such as the type of the administered immunosuppressive modality, obesity, ethnicity, hypomagnesemia, cytomegalovirus (CMV), and hepatitis C viral (HCV) infections. Early identification and adjustment of the risk factors for these modalities might be associated with significant improvement in prognostic outcomes. The most commonly diagnosed post-transplant carcinomas, including renal cell carcinoma, squamous cell cancer of the lip and skin, salivary gland cancer, and cholangiocarcinoma. Besides, HCV, CMV, and BK virus were the most commonly reported infections following kidney transplantation.